2014
DOI: 10.1186/2045-7022-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to airborne allergens among adults and its impact on allergic symptoms: a population survey in northern Vietnam

Abstract: BackgroundThe knowledge about allergic sensitization and its relationship with clinical symptoms and diseases among adults in South-East Asia is poor. The aim of this study was to investigate the prevalence and pattern of allergic sensitization and the association with asthma and allergic rhinitis in adults in urban and rural Vietnam.MethodsAmong 5,782 responders to a questionnaire survey in northern Vietnam, a random sample was invited to a clinical follow-up and 684 (46%) participated. The methods included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 29 publications
8
31
2
Order By: Relevance
“…Impact of pollen on the quality of life is associated with both pollen load in a territory (Fereidouni et al 2010;Velasco-Jiménez et al 2014) and lifestyle (Kiotseridis et al 2013;Lâm et al 2014). Lithuania belongs to the group of countries in which pollen of It was demonstrated in the study carried out during 2013-2014 that pollen concentrations in adjacent years can be significantly different, and prevention of diseases associated with airborne pollen becomes more difficult due to this factor.…”
Section: Discussionmentioning
confidence: 98%
“…Impact of pollen on the quality of life is associated with both pollen load in a territory (Fereidouni et al 2010;Velasco-Jiménez et al 2014) and lifestyle (Kiotseridis et al 2013;Lâm et al 2014). Lithuania belongs to the group of countries in which pollen of It was demonstrated in the study carried out during 2013-2014 that pollen concentrations in adjacent years can be significantly different, and prevention of diseases associated with airborne pollen becomes more difficult due to this factor.…”
Section: Discussionmentioning
confidence: 98%
“…Also, other studies have found stronger associations between allergic sensitization and rhinitis than with asthma. 28,29 It is well known that asthma is also associated with several environmental factors including smoking and traffic exhausts, socioeconomic status, and obesity, whereas rhinitis has been mainly associated with allergic sensitization. 15,27,29 In a multivariate model including all major specific allergens, sensitization to timothy, birch, and cat remained significantly associated with allergic rhinitis, whereas sensitization to horse and dog did not become significant.…”
Section: Discussionmentioning
confidence: 99%
“…The wheal diameter was measured as the average of the largest wheal diameter and its perpendicular. The test result was considered positive if the mean wheal diameter was ≥3 mm [17]. Allergens included pollen, house dust mites, dust mites, feathers, insects, grasses, weeds, and latex.…”
Section: Methodsmentioning
confidence: 99%